PEMAKNAAN DAN TRANSMISI MANTRA TRI SANDHYA PADA REMAJA HINDU BALI DI DAERAH MALANG - Candra, Khairul; Noviyanti, Luh Putu Ema; Nurlaily, Kiki (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2018)
This paper reviews the meaning and transmission of Tri sandhya mantra.Mantra Tri Sandhya is one form of oral literature in Bali. Mantra Tri Sandhya is a mantra owned by Balinese Hindus used in everyday life. At this moment, the Tri Sandya spell is being forgotten and rarely used by Balinese Hindu teenagers. Based on this background, this study was conducted to (1) know the meaning of Tri Sandhya mantra: (2) Tri Sandhya spell transmission on Balinese Hindu adolescents living in Malang. The method used in this research is descriptive qualitative method. The method used in this study to obtain data in the form of sentences instead of numbers. The data source of this research is Mantra Tri Sandhya. This research uses Semiotics approach with Riffaterre theory. Semiotics is used to examine the signs that exist in the Tri Sandhya spell so readers can understand the meaning of the Tri Sandhya spell. The results of this study indicate that the meaning of Tri Sandhya mantra and Tri Sandhya spell transmission on Balinese Hindu adolescents in Malang region today.